An Ab initio study of oxygen vacancies and doping process of Nb and Cr atoms on TiO2 (110) surface models - Sambrano, J. R. [UNESP]; Andrés, J.; Beltrán, A.; Sensato, F. R.; Leite, E. R.; Stamato, F. M.L.G.; Longo, E. (My University, 1997)
We theoretically investigated how the formation of oxygen vacancies and the addition of niobium and chromium atoms as dopants modify the varistor properties of TiO2. The calculations were carried out at the HF level using a contracted basis set, developed by Huzinaga et al., to represent the atomic centers on the (110) surface for the large (TiO2)15 cluster model. The change of the values for the net atomic charges and band gap after oxygen vacancy formation and the presence of dopants in the lattice are analyzed and discussed. It is shown that the formation of oxygen vacancies decreases the band gap while an opposite effect is found when dopants are located in the reduced surface. The theoretical results are compared with available experimental data. A plausible explanation of the varistor behavior of this system is proposed. © 1997 John Wiley & Sons, Inc.
Keywords: Ab initio; Doping; Oxygen vacancy; Titanium oxide surface; Varistor ceramics